Career adaptability of international hospitality management students during the COVID-19 pandemic: Focus on the role of language communication competence. (March 2023) - Ren, Shuang; Islam, Mohammad Tarikul; Chadee, Doren
Abstract: In addition to dealing with language, communication and cultural barriers, international students in hospitality management were suddenly confronted with bleak career prospects in a sector crippled by the COVID-19 pandemic. Yet, little is known about how international students in hospitality management mobilize personal resources to cope with sudden career shock events. We address this question by developing and testing a model of career adaptability of international hospitality management students during the COVID-19 pandemic that focuses on the role of language communication competence. We draw from communication theory to argue that language communication competence enables international hospitality management students to appraise COVID-19 as presenting career opportunities that in turn motivate career adaptability contingent on cultural distance. Our results, based on a sample (n = 290) of international hospitality management students in Australia during the COVID-19 pandemic, support our contention. The theoretical and practical implications of our findings of the role of communicative behavior and cultural competence for coping with career transitions in periods of crises are fully discussed.